Use of aromatase inhibitors to treat endometriosis-related pain symptoms: a systematic review - Venturini Pier L; Gillott David J; Ferrero Simone; Remorgida Valentino (Reproductive Biology and Endocrinology, 2011)
Abstract This systematic review aims to assess the efficacy of aromatase inhibitors (AIs) in treating pain symptoms caused by endometriosis. A comprehensive literature search was conducted to identify all the published studies evaluating the efficacy of type II nonsteroidal aromatase inhibitors (anastrozole and letrozole) in treating endometriosis-related pain symptoms. The MEDLINE, EMBASE, PubMed, and SCOPUS databases and the Cochrane System Reviews were searched up to October 2010. This review comprises of the results of 10 publications fitting the inclusion criteria; these studies included a total of 251 women. Five studies were prospective non-comparative, four were randomized controlled trials (RCTs) and one was a prospective patient preference trial. Seven studies examined the efficacy of AIs in improving endometriosis-related pain symptoms, whilst three RCTs investigated the use of AIs as post-operative therapy in preventing the recurrence of pain symptoms after surgery for endometriosis. All the observational studies demonstrated that AIs combined with either progestogens or oral contraceptive pill reduce the severity of pain symptoms and improve quality of life. One patient preference study demonstrated that letrozole combined with norethisterone acetate is more effective in reducing pain and deep dyspareunia than norethisterone acetate alone. However, letrozole causes a higher incidence of adverse effects and does not improve patients' satisfaction or influence recurrence of symptoms after discontinuation of treatment. A RCT showed that combining letrozole with norethisterone acetate causes a lower incidence of adverse effects and lower discontinuation rate than combining letrozole with triptorelin. Two RCTs demonstrated that, after surgical treatment of endometriosis, the administration of AIs combined with gonadotropin releasing hormone analogue for 6 months reduces the risk of endometriosis recurrence when compared with gonadotropin releasing hormone analogue alone. In conclusion, AIs effectively reduce the severity of endometriosis-related pain symptoms. Since endometriosis is a chronic disease, future investigations should clarify whether the long-term administration of AIs is superior to currently available endocrine therapies in terms of improvement of pain, adverse effects and patient satisfaction.